The lost story ebook A novel. - Shaffer, Meg (2024)
NATIONAL BESTSELLER • Inspired by C. S. Lewis’s The Chronicles of Narnia, this wild and wondrous novel is a fairy tale for grown-ups who still knock on the back of wardrobes—just in case—from the author of The Wishing Game . “This is the book you’ve been waiting for.”—Richard Russo, Pulitzer Prize–winning author of Empire Falls and the North Bath Trilogy AN NPR BEST BOOK OF THE YEAR As boys, best friends Jeremy Cox and Rafe Howell went missing in a vast West Virginia state forest, only to mysteriously reappear six months later with no explanation for where they’d gone or how they’d survived. Fifteen years after their miraculous homecoming, Rafe is a reclusive artist who still bears scars inside and out but has no memory of what happened during those months. Meanwhile, Jeremy has become a famed missing persons’ investigator. With his uncanny abilities, he is the one person who can help vet tech Emilie Wendell find her sister, who vanished in the very same forest as Rafe and Jeremy. Jeremy alone knows the fantastical truth about the disappearances, for while the rest of the world was searching for them, the two missing boys were in a magical realm filled with impossible beauty and terrible danger. He believes it is there that they will find Emilie’s sister. However, Jeremy has kept Rafe in the dark since their return for his own inscrutable reasons. But the time for burying secrets comes to an end as the quest for Emilie’s sister begins. The former lost boys must confront their shared past, no matter how traumatic the memories. Alongside the headstrong Emilie, Rafe and Jeremy must return to the enchanted world they called home for six months—for only then can they get back everything and everyone they’ve lost.